(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Adenoid vegetations are among the most common upper respiratory tract disorders in children. The aim of this study was to investigate the expression of the Bcl-2 immunohistochemical marker in different morphological forms of adenoid vegetations and to evaluate its diagnostic significance. Adenoid tissue samples were examined using morphological and immunohistochemical methods. Bcl-2 expression was compared among different forms of adenoid hypertrophy. The highest expression was observed in the angiomatous form, whereas lower expression levels were found in the interstitial proliferative inflammatory and sclerotic forms. The findings suggest that Bcl-2 may serve as an additional diagnostic marker for the morphological assessment of adenoid vegetations.